PERAN DESAIN LABEL DAN MEDIA SOSIAL DALAM MENGEMBANGKAN USAHA TEMPE LOKAL DI DESA LEMBA HARAPAN - Nurul Viana; Putri Tordon; Trisna Trisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Tempeh is one of Indonesia's traditional foods that holds high nutritional value and significant economic potential, especially when managed by Micro, Small, and Medium Enterprises (MSMEs). This community service activity focused on the development of local tempeh businesses in Lemba Harapan Village, South Dampal District, Tolitoli Regency, to enhance MSME capacity through strengthening product identity and utilizing social media as a means of digital promotion. The implementation method employed a participatory and educational approach, including field surveys, label design, technical assistance in label application, and training on social media management. The results of the activity showed that business actors successfully developed a product identity in the form of business labels and logos, acquired basic skills in branding, and utilized social media to expand their marketing reach. Furthermore, the active involvement of business owners in each stage of the activity indicated increased motivation and independence in developing their businesses. This initiative has had a positive impact on strengthening the competitiveness of local tempeh businesses. The simple yet targeted mentoring model can be replicated in other micro-enterprises as a strategy to support MSME empowerment and sustainable rural economic development.